Assessment of Anaerobic Bioreactors with Different Sizes of Powdered Activated Carbon and Hybrid Membrane in Treating Palm Oil Mill Effluent. - Tai, Chee Yong (2016)
In this study, different sizes of powder activated carbon (PAC) was added into four identical anaerobic bioreactors (AnMBRs) to investigate their effects on chemical oxygen demand (COD) removal, natural organic matters (NOM) removal, mixed liquor suspended solid (MLSS), mixed liquor volatile suspended solid (MLVSS) and membrane fouling control. With decrease of PAC sizes, the MLSS and MLVSS in the AnMBRs had increased which led to higher COD removal rate (89.45 ± 2.48%), bigger floc size (62.815 ± 1.450µm), lower NOM content (1133 ± 552 mg/L for protein and 75 ± 3 mg/L for polysaccharide) and better membrane fouling control. In addition, to investigate the performance of polyethersulfone (PES) membrane in fouling control, different concentrations of PAC had been incorporated into it. Results shows that by incorporating 5 %wt of PAC into the PES membrane, it shows better in performance. The hybrid membranes show positive results in COD removal (95.77 ± 0.27%), membranes fouling control and could produce higher quality of permeate.